2016
DOI: 10.1111/2041-210x.12675
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic description of population dynamics using dynamic energy budget theory incorporated into integral projection models

Abstract: Summary1. Integral projection models (IPMs) provide a powerful approach to investigate ecological and rapid evolutionary change in quantitative life-history characteristics and population dynamics. IPMs are constructed from functions that describe the demographic rates -survival, growth and reproduction -in relation to the characteristics of individuals and their environment. Currently, however, demographic rates are estimated using phenomenological regression models that lack a mechanistic representation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 26 publications
1
99
0
Order By: Relevance
“…Predictions from the DEB‐IPM matched this overall population response, from which we infer that our cross‐level test on overall population performance was satisfactory. The model therefore likely captures the overall effect of density dependence through food exploitation very well, as population equilibrium is reached across the combinations of expected feeding levels of which we know are close to levels for which we observe population equilibrium in our experimental populations (Smallegange et al., : Appendix S1). In addition, the more general analysis of population performance across a wide range of stochastic environments showed that the pattern of a small reduction in average fitness under large‐adult harvesting persisted across different noise colours and frequencies of good environments.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Predictions from the DEB‐IPM matched this overall population response, from which we infer that our cross‐level test on overall population performance was satisfactory. The model therefore likely captures the overall effect of density dependence through food exploitation very well, as population equilibrium is reached across the combinations of expected feeding levels of which we know are close to levels for which we observe population equilibrium in our experimental populations (Smallegange et al., : Appendix S1). In addition, the more general analysis of population performance across a wide range of stochastic environments showed that the pattern of a small reduction in average fitness under large‐adult harvesting persisted across different noise colours and frequencies of good environments.…”
Section: Discussionsupporting
confidence: 65%
“…For example, tools like bifurcation analysis can now be used to study model dynamics as a function of the values of these life‐history traits (e.g. Smallegange et al., : Appendix S1) so that one could e.g. ask “at what maximum length or mortality rate do abrupt changes, like from population stability to extinction, occur?” Such analyses could be particularly insightful when investigating the intricacies of life‐history effects on population dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations